Prolonged Screen Exposure During COVID-19—The Brain Development and Well-Being Concerns of Our Younger Generation - Wong, Agnes S. K. (Frontiers in Public Health, 2021)
COVID-19 is a significant public health crisis and it has given a major impact especially in the field of education. The situation has forced educators around the world to shift to an online mode of teaching and children are forced to study online at home. The benefits of online learning are undeniable, but the possible long-term developmental risks of prolonged screen use should not be overlooked. Recent research findings have clearly suggested the negative effects of screen time on the brain development and well-being of our younger generation. Considering the possible long-term developmental risks of prolonged screen use, policy makers should consider appropriate public health policy (e.g., recommendations on screen time) and guideline for the implementations of online learning (e.g., allowing flexibility to suit individual needs). Multidisciplinary collaboration between policy makers, health care professionals, schools, and parents is required to rethink the current situation before it is too late.